Control Mechanisms in Service Outsourcing Relationships in the Public Sector - Neves, Tiago (2022)
Objective: analyze the role of management control mechanisms in service outsourcing relationships in the public sector, considering the challenges of cooperation and coordination of activities. Method: qualitative research, based on interviews, a questionnaire, and triangulation of these data with documents, supported by a case study in a decentralized unit of the Public Ministry of Labor, with the analysis of outsourced cleaning and conservation services. Results: the services analyzed do not use specific assets, operate in an environment of moderate uncertainty, have easy-to-measure, and note very complex tasks, in addition to having moderate interdependence between the contracting organization and the contracted organizations. the use of formal and informal control instruments was observed. The results also suggest that the bureaucratic environment of these contracts can influence the configuration of management control mechanisms, with little flexibility for activities or relationships to develop beyond contractual terms. Originality/Relevance: the study contributes to the advancement of the scientific debate on the subject in public organizations and the Brazilian context. Theoretical/methodological contributions: the work adds to the literature by approaching the configuration of management control mechanisms in supplier-buyer relationships in public organizations. Social/management contributions: the results can help public sector organizations to understand the aspects that influence the configuration of the control system of their outsourced service contracts, in addition to encouraging discussions about the challenges of these contracts.